Apoptosis in Hormone-Dependent Cancers - Tenniswood, Martin; Michna, Horst 1954-2007 (Ernst Schering Foundation Symposium Proceedings, 1995)
It is now widely accepted that cells have the ability to initiate a program of gene-directed death, a process called "apoptosis" which may also be used as an innovative strategy for therapeutic intervention in cancer therapy. Experts in this area report on the regulation and control of apoptosis in hormone dependent (neoplastic) tissue and the possibility to exploit active cell death for therapeutic application